The Fiscal Case Against Statehood: Accounting for Statehood in New Mexico and Arizona - Moussalli, Stephanie D. (Lexington Books, 2012)
New Mexico and Arizona joined the Union in 1912, despite the opposition from some of their residents. The Fiscal Case against Statehood examines the concerns of the people who lost the battle over statehood in the two territories. Moussalli examines their territorial and early state governments’ fiscal behavior and reveals that while their fears of steep increases in the cost of government were well-founded, statehood also significantly improved their governments’ accountability for their use of the public purse. She concludes that fiscal officials enabled statehood’s growth in government by improving the financial reports and processes. Moussalli examines New Mexico’s and Arizona’s financial reports before and after statehood, and compares them to the state of Nevada’s reports as a control. Through detailed, systematic analysis, Moussalli reveals the fiscal costs and accountability gains of statehood for the residents of New Mexico and Arizona.